Educação, trabalho e universidade: o que pensam os estudantes de liceus de Fortaleza? - Miranda, Régis Wendel Gomes (2015)
The secondary school has the responsibility to deal with the need of development of individuals prepared to exercise citizenship, university and labour market admittance. This step of school development has the function of qualify the young people for the construction of your future and transformation of your society. However the high levels of school evasion as well disapproval reflect the difficulty on secondary school to deal with students wishes and living conditions. Therefore, this study aim comprehend the meanings and expectations that the young construct about secondary school from your school experiences and social realities. The methodological instruments used were survey, interviews and the systematic observation of social relationships at two public schools on the state of Ceará, they are Liceu de Messejana and Liceu do Conjunto Ceará. The results of the research identify the dilemmas lived by students inside and outside school context, considering the category school, work and university, that are driven by various interested ones, like the governments, families, professionals and students. For that reason, were explored the students and their families profile, as their perception about work and professional experiences, besides perceiving their opinions about school and secondary school.